2012
DOI: 10.1016/j.neuron.2012.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Oscillatory Neural Ensembles for Rules in the Prefrontal Cortex

Abstract: SUMMARY Intelligent behavior requires acquiring and following rules. Rules define how our behavior should fit different situations. To understand its neural mechanisms, we simultaneously recorded from multiple electrodes in dorsolateral prefrontal cortex (PFC) while monkeys switched between two rules (respond to color versus orientation). We found evidence that oscillatory synchronization of local field potentials (LFPs) formed neural ensembles representing the rules: there were rule-specific increases in sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
369
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(413 citation statements)
references
References 57 publications
32
369
2
1
Order By: Relevance
“…In our task, the cue signified a color-matching rule ("find the peripheral stimulus matching the color of the cue and enhance its representation against other stimuli"). Correctly interpreting the cue required reactivating neural assemblies coding for the rule representation and applying the rule to the visually available information to eventually prioritize processing of the attended stimulus and filter out uncued stimuli (3,38) (Fig. S8A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our task, the cue signified a color-matching rule ("find the peripheral stimulus matching the color of the cue and enhance its representation against other stimuli"). Correctly interpreting the cue required reactivating neural assemblies coding for the rule representation and applying the rule to the visually available information to eventually prioritize processing of the attended stimulus and filter out uncued stimuli (3,38) (Fig. S8A).…”
Section: Discussionmentioning
confidence: 99%
“…We thus correlated burst-LFP synchronization of neurons recorded at LFP recording sites that provided theta-phase or gamma-amplitude variations for theta-gamma correlations (SI Result S13). We found that burst synchronization to remote LFP gamma activity varied proportionally with the degree of theta-phase correlation with low-gamma amplitudes (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50), an effect that was limited to those LFP sites that showed significant theta-gamma correlations (Spearman rank correlation r = 0.2, P = 0.044; Table S2 and SI Result S13). To our knowledge, these findings provide the first quantitative evidence that recording sites with LFP theta phases that engage in longrange gamma correlations also host neurons whose burst firing events synchronize long-range to gamma activity.…”
Section: Theta-gamma Correlation and Its Relation To Synchronization Ofmentioning
confidence: 95%
“…
Studies of neural oscillations in the beta band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) have demonstrated modulations in beta-band power associated with sensory and motor events on time scales of 1 s or more, and have shown that these are exaggerated in Parkinson's disease. However, even early reports of beta activity noted extremely fleeting episodes of beta-band oscillation lasting <150 ms. Because the interpretation of possible functions for beta-band oscillations depends strongly on the time scale over which they occur, and because of these oscillations' potential importance in Parkinson's disease and related disorders, we analyzed in detail the distributions of duration and power for beta-band activity in a large dataset recorded in the striatum and motor-premotor cortex of macaque monkeys performing reaching tasks.
…”
mentioning
confidence: 99%
“…Furthermore, a recent study of lateral PFC-mediated control processes in monkeys found beta-range oscillations associated with task-relevant rule selection, and alpha oscillations with the unselected rule (Buschman et al, 2012). In humans, beta oscillations are implicated in the control of both movement and cognition by 'endogenous', top-down processes that are usually synonymous with cognitive control (reviewed in Engel and Fries, 2010), and likely mediated via fronto-striatal circuitry (Jenkinson and Brown, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Rule selection and representation is a critical element of cognitive control, as it guides taskor context-appropriate responses to the environment (Bunge, 2004). Studies in monkeys have identified how cortical oscillations support rule-representation, including theta (Benchenane et al, 2010;Womelsdorf et al, 2010), alpha and, beta in both rule acquisition (Benchenane et al, 2011) and rule selection (Buschman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%